The audit as prevention of environmental risk in the agroindustries of La Libertad – 2021 - Torres Salas, Theo Christian (2022)
The planning of environmental audits is very important as a contribution to the environmental management of the agro-industrial companies of Trujillo and Virú, provinces of La Libertad, which are located on the north coast of Peru. As part of the investment in environmental risk prevention, these audits are planned and carried out regularly to timely detect the risks inherent to its operations. A year, more than 10 days are used to carry out these audits. Regarding the audits and the cost, they represent, there is an inversely proportional relationship, since they represent less than 20% of the budget in investment in prevention, however, the great value in them is recognized in terms of their results, which are taken to improve compliance with the applicable environmental legal framework, especially the one on which agro-industrial companies are supervised. Some factors that have been relevant in relation to audits and risk prevention have been regulatory changes in the agribusiness sector, the duration of the pandemic, the demands of interested parties, and the qualification and experience of the auditors who carried out the audits. and allowed to detect those relevant elements on which to act.